Gastronomi Jerman sebagai Representasi Identitas Budaya - Irma Liani; Cahaya Mustika; Chairunnisa Nasution; Greace Simaremare (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
Gastronomy is not merely understood as an act of consumption but also as a cultural system that reflects the social identity, history, and geographical conditions of a society. This study analyzes German gastronomy as a representation of cultural identity through three main elements: Bratwurst, Brotkultur, and Bierkultur. The research employs a descriptive qualitative approach through a literature review of gastronomic studies, European food culture research, and academic sources on the history of German cuisine. The analysis is conducted by situating food within historical, geographical, and socio-cultural frameworks to examine the formation of culinary identity. The findings indicate that these three elements do not represent a homogeneous identity; rather, they are the result of cultural constructions rooted in regional diversity and historical processes, including commercialization and traditional regulations such as the Reinheitsgebot. Therefore, German gastronomy functions as a medium for articulating cultural identity, shaped through the interaction of history, geography, and social dynamics.